Sistema Integrado de Respostas Técnicas - SIRT: trajetória, papel institucional e desafios contemporâneos - Carvalho, Beatriz Leal de (2023)
SBRT is especially developed for micro and small companies – MPEs, legally constituted, and that demanded technical solutions. Its objective is to facilitate rapid access to low-complexity technological solutions in specific areas, in addition to promoting the dissemination of knowledge and contributing to the technology transfer process, especially for smaller companies (RAMOS et al., 2006). To meet the objectives set, the SBRT was created as a network made up of nine technical response agents, with “specialists from institutions with recognized performance in innovation and technology, which prepare quick answers to the most diverse technical questions free of charge” (SBRT, 2023). One of the executing agents of this network is the Integrated System of Technical Responses, linked to the Universidade Estadual Paulista Júlio de Mesquita Filho (SIRT/UNESP), the object of study on this research. The SIRT has not yet been the subject of more in-depth investigation. Therefore, this can be treated as a justification for carrying out this research, which was guided by the following question: what are the institutional and operational characteristics of the SIRT and its historical contributions as an agent of technical responses to the SBRT? The main objective of the research is to evaluate the impacts of SIRT as a manager of knowledge and low-complexity innovations in the period between 2010 and 2023. To achieve this objective, the research covered the following specific objectives: i) map and record the historical evolution and structural (agents) and operational (products) changes in SIRT; ii) analyze local impacts regarding the university-governmentbusiness relationship and iii) characterize the results generated in knowledge management for SBRT. To achieve the proposed objectives, a qualitative approach was chosen from a historical, exploratory and descriptive perspective, framed as a single case study, adopting documentary research as the main data collection instrument. For data processing, document analysis was defined. Regarding the results, focused on the trajectory, institutional role and contemporary challenges of the SIRT, it was found that it presented positive results, fulfilling the objectives initially outlined in terms of knowledge management. Furthermore, among the positive results it is important to consider the intense development of the university tripod of teaching, research and extension, developed over the years of SIRT operation. In addition to this, it is also necessary to consider the contribution of SIRT to the effectiveness of the triple helix in the joint action of UNESP, the State, municipal entities and MSEs. It is also necessary to emphasize that data control, document gaps, the lack of situational analysis and the absence of indicators are weak points in the operationalization of the service and that deserve attention not only from the SIRT, but also from the SBRT Network. Furthermore, for effective intellectual, social and economic development to be possible, effective support from the State is essential. This is because, as presented in this research, the integral development of Brazil, whether due to its productive characteristics, territorial size or the needs resulting from these factors, urgently demands the prioritization of MSEs and the establishment of solid cooperation networks that consider all agents social.